CD73-mediated adenosine production by CD8 T cell-derived extracellular vesicles constitutes an intrinsic mechanism of immune suppression - Enja Schneider; Riekje Winzer; Anne Rissiek; Isabell Ricklefs; Catherine Meyer-Schwesinger; Franz L. Ricklefs; Andreas Bauche; Jochen Behrends; Rudolph Reimer; Santra Brenna; Hauke Wasielewski; Melchior Lauten; et al. (Nature Communications, 2021)
Ectonucleotidases associated to regulatory T cells are known modulators in the inflammatory environment. Here the authors describe CD8 T cell-derived extracellular vesicles bearing CD73 and suggest they function as an additional intrinsic modulator of immune responses.